ACUTE MASTOIDITIS: WHY MANDATORY IMMUNIZATION IS IMPORTANT? - Makević Đurić, Mirjana; Djurić, Milivoje; Rakovic, Biljana (HEALTH CARE, 2025)
Introduction/Aim. Acute mastoiditis (AM) is a serious bacterial infection of the mastoid bone that occurs as a consequence of acute otitis media (AOM). Although mastoiditis can occur at any age, the majority of patients are less than two years of age, with a median age of 12 months. The infection is most often caused by Streptococcus pneumoniae. After antibiotics and pneumococcal vaccination, 0,002% of children with AOM progress too acute coalescent mastoiditis. The aim of this study is to present the case of a four-year-old girl with AM who was found not vaccinated by pneumococcal conjugated vaccine according to the mandatory immunization schedule of the Republic of Serbia.Case report. We describe the case of a four-year-old girl with AM, where we found that she was not regularly vaccinated by pneumococcal conjugated vaccine. The girl was presenting with irritability, fussiness, fever, ear pain, red and swollen retroauricular skin. The inflammatory markers were elevated. Due to the suspicion of acute mastoiditis, a CT scan of the endocranium was performed, which confirmed the diagnosis. Timely initiation of parenteral antimicrobial therapy with surgical retroauricular incision and drainage of the periosteal abscess, mastoidectomy and myringotomy perfomed on the girl led to an improvement in the general condition, and Streptococcus pneumoniae was isolated in the drained contents. Conclusion. By presenting the case of an unvaccinated child who suffered from acute mastoiditis caused by a vaccine preventable disease we once again wanted to draw attention to the importance of timely immunization.
Keywords: acute mastoiditis, Streptococcus pneumoniae, pneumococcal conjugate vaccine, mandatory immunization